Spaces for support: Discursive negotiations of supporter positions in online forum discussions about suicide. (October 2018) - Lundström, Ragnar
Abstract: This article investigates self-organized peer-to-peer support in online forum discussions about suicide. It analyzes how the discursive strategies through which participants introduce themselves as supporters relate to the support they provide. The analysis shows that the strategies employed to construct supporter identities commonly draw on what has been described as 'somatic individuality' – by which the management of biological 'risks' are framed as individual responsibilities – and by negotiating tensions between different perspectives on suicide. These are; (a) a discourse focusing on psychiatric knowledge and psychopharmaceuticals (b) a discourse focusing on social context and personal relationships, and (c) a critical stance towards the established care system. Negotiations between these condition, and are also conditioned by, power relations in the forum. These dynamics regulate the ways in which participants can use an online forum in order to move away from crisis points by discursively attempting to enter a supporter position. Highlights: Supporter positions often draw on what has been described as 'somatic individuality'. Supporter legitimacy is linked to negotiating different perspectives on suicide. These negotiations are marked by hierarchies and power relations in the forum.